BS62 Myocardial fibrosis and the degree of gap junction coupling directly modifies the underlying mechanism of fibrillation. (May 2019) - Handa, Balvinder; Li, Xinyang; Mansfield, Catherine; Jabbour, Richard J; Pitcher, David; Chowdhury, Rasheda A; Peters, Nicholas; Ng, Fu Siong
Abstract : Background: Mechanisms that maintain ventricular fibrillation (VF) remain debated. There are data supporting both critical areas sustaining rotational drivers (RDs) and the contrary hypothesis of disorganised myocardial activation driving VF. Abnormal electrical coupling between cardiomyocytes through gap junctions (GJ) and ventricular fibrosis are major factors in disease related remodelling, and have been implicated in initiation and maintenance of VF. In this study we hypothesised that the mechanism of VF is directly altered by fibrosis and GJ coupling, and that modulating these factors shifts or changes the predominant mechanism of fibrillation along the spectrum between disorganised activity and organised drivers. Methods: VF optical mapping was performed in fifty-five perfused rat hearts with differing degrees and patterns of chronic ventricular fibrosis [compact (CF, n=11), patchy (PF, n=13) and diffuse (DF, n=11)], and acute GJ coupling modulation with rotigaptide (RTG, GJ coupling enhancer, 0–80nM, n=10) or carbenoxolone (CBX, GJ uncoupler, 0–50μM, n=10). Fibrillation dynamics were quantified using phase analysis, RD tracking and our novel method of global fibrillation organisation quantification, frequency dominance index (FDI), which is defined as the power ratio of highest amplitude dominant frequency in the frequency spectrum. Results: In the fibrosis group, VF was driven predominantly by disorganised activity in CF, RDs were detected 26±7% of time comparative to 51.2±4% in DF and 69.5±8% in PF group (p=0.001). PF stabilised RDs, average maximum rotations for a single RD in PF were 31.6±7.1 comparative to 12.5±1.7 in DF and 6.4±1.1 in CF, p<0.001. VF organisation measured by FDI was higher in PF (PF: 0.61±0.07, DF: 0.47±0.04, CF: 0.33±0.03, p=0.004) (figure 1 ). In the GJ modulation group, maximum rotations for a RD increased with RTG (0nm: 5.4±0.45 vs 80nM: 48.20±12.32, p<0.001) and decreased with CBX (0μM: 8.0±1.3 vs 50μM: 0.3±0.3, p<0.001). Proportion of time RDs were detected in VF increased with RTG (0nM: 44±6 vs 80nM: 93±2, p<0.001) and decreased with CBX (0μM: 61±9% vs 50μM: 3±2%, p<0.001). FDI increased with RTG (0nM: 0.53±0.04 vs 80nM: 0.78±0.3, p<0.001) and decreased with CBX (0μM: 0.60±0.05 vs 50μM: 0.17 ±0.03, p<0.001) (figure 2 ). Conclusion: VF mechanisms occur along a spectrum between organised activity with discrete drivers and disorganised myocardial activation. The degree of GJ coupling and ventricular fibrosis are key determinants of the underlying mechanism of VF. Enhanced GJ coupling and patchy fibrosis organised fibrillation and stabilised RDs, whilst GJ uncoupling and compact fibrosis disorganised VF. This study presents a unifying explanation for the numerous mechanisms reported for sustaining fibrillation. Characterising the degree and pattern of fibrosis in patient groups vulnerable to VF might be beneficial in identifying patients with targetable substrate, and GJ modulation might be a potential therapeutic target. Conflict of interest: Nil